Functionalized Glutathione on Chitosan-Genipin Cross-Linked Beads Used for the Removal of Trace Metals from Water - Samira R. Akaji; David Dewez (International Journal of Biomaterials)
Functionalized glutathione on chitosan-genipin cross-linked beads (CS-GG) was synthesized and tested as an adsorbent for the removal of Fe(II) and Cu(II) from aqueous solution. The beads were characterized by several techniques, including Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), CNS elementary analysis, scanning electron microscopy (SEM), and atomic force microscopy (AFM). The effect of several parameters such as the pH, the temperature, and the contact time was tested to optimize the condition for the adsorption reaction. The beads were incubated in aqueous solutions contaminated with different concentrations of Fe(II) and Cu(II) (under the range concentration from 10 to 400 mg·L−1), and the adsorption capacity was evaluated by inductively coupled plasma optical emission spectrometry (ICP-OES). The adsorption equilibrium was reached after 120 min of incubation under optimal pH 5 for Fe(II) and after 180 min under optimal pH 6 for Cu(II). According to the Langmuir isotherm, the maximum adsorption capacities (qmax) for Fe(II) and Cu(II) were 208 mg·g−1 and 217 mg·g−1, respectively. Our results showed that the adsorption efficiency of both metals on CS-GG beads was correlated with the degree of temperature. In addition, the adsorption reaction was spontaneous and endothermic, indicated by the positive values of ΔG0 and ΔH0. Therefore, the present study demonstrated that the new synthesized CS-GG beads had a strong adsorption capacity for Fe(II) and Cu(II) and were efficient to remove these trace metals from aqueous solution.